PENGARUH LINGKUNGAN KERJA INTERNAL DAN LINGKUNGAN KERJA EKSTERNAL TERHADAP PRESTASI KERJA PEGAWAI SEKRETARIAT KORPRI SANGATTA - Dewi, Aji Ayudhia (EKONOMIA, 2014)
This study was to determine the effect of the internal work environment and external work environment on employee performance KORPRI Sengata Secretariat.Research problem as follows: the internal work environment and external work environment whether working environment will affect the performance, while the goal is to analyze the influence of the position based on the level of the explanatory variables studied by analysis of the study are employees of the Secretariat KORPRI Sengata. This research includes the study population by the number of 42 employees. The test questionnaire before conducting research data collection. Test equipment used in this study to use your test 1. linear regression analysis of the independent variable 2 determinant coefficient (R2) 3 F test and t test 4.From equation can be explained bahwa1,866 means job performance (Y) with no variables, whereas 0,445 (X1) there is a change on the performance improvement, 0.443 means there is a change or addition to the internal work environment and external work environment, there will be additional increase in performance (Y) by assuming other variables remain constant. This means that if one among the independent variables plus of one unit will contribute to the performance assuming other variables constant.The conclusion of this study is to answer the hypothesis of the proposed formulation of the problem where the internal work environment variables have a dominant influence on employee performance KORPRI Sengata Secretariat.